ANALISIS PENGELOLAAN PAJAK DAERAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) DI KOTA BINJAI - Putri, Diva Aulia; Junawan, Junawan; Adiman, Sumardi (Universitas Pembangunan Panca Budi, 2024)
This research aims to find out how regional taxes are managed, targets and realization of regional taxes and how effective regional taxes are in increas-ing local revenue in the Binjai city government. The method used in this research is quantitative descriptive. The data collection technique is through primary data, namely data obtained directly from data sources where the research was carried out at BPKPAD Binjai City and secondary data, namely data ob-tained through literature study. The results of the research show that the regional tax realization results obtained each year are not in accordance with the specified targets, resulting in a decline. with an average of 64.6%. Based on the effectiveness level, the results of the target percentage and realization of regional taxes are still below 100% with an average of 64.6% with the Ineffective (TE) criteria. It is hoped that BPKPAD will be able to manage regional taxes and explore the potential of Binjai City so that regional tax revenues can exceed the specified targets and can increase Orig-inal Regional Income.